The Practice of Total Quality Management in Selected Laboratories in Port Harcourt, Nigeria - G. A, Nwankwo,; O, Joel,; O. M. O, Etebu,; G, Abu. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
The objective of this study is to determine the extent of total quality management practice in selectedlaboratories in Rivers State, Nigeria. The data for the study were collected from 600 laboratorypersonnel using a self-developed, pre-tested, validated and reliable questionnaire. The participantswere from the universities, industries, government and private owned medical laboratories. Theresults were standardized to 100%. The desired extent of total quality management practice wasbenchmarked at greater than 75%. The results of this study showed that there was below 75% in theextent of total quality management practice in the selected laboratories (59.64±6.72) in PortHarcourt, Nigeria. The extent of total quality management practice was below the expected standard.Efforts should be made to improve the extent of laboratory total quality management in PortHarcourt metropolis, Nigeria. This can be achieved through organized trainings, re-trainings,advocacy, customers and employees focus, and aggressive top management involvement onlaboratory total quality management system.